Mathematical Literacy Ability and Adversity Quotient in Climber Type Students - Ratna Fertikawati; Gunawan Gunawan (UM Purwokerto Press, 2025)
This study aims to describe the mathematical literacy skills and Adversity Quotient (AQ) of students with the Climbers type. Mathematical literacy is an essential skill in modern education that enables students to understand and apply mathematical concepts in everyday activities. Meanwhile, Adversity Quotient represents a person's ability to face and overcome obstacles. This study employs a descriptive qualitative approach involving 36 students from seventh grade at SMP Negeri 2 Mandiraja as research subjects. Data were collected through the Adversity Response Profile (ARP) questionnaire, written tests on mathematical literacy skills, and interviews with the research subjects. The findings indicate that Climbers type students possess high mathematical literacy skills, supported by a high Adversity Quotient. They are capable of formulating information, employing problem-solving strategies, and explaining the results obtained. The study concludes that Climbers type students have good mathematical literacy skills and suggests that further research be conducted to explore learning media that can support the learning process for Climbers type students.